Bridging Modern Medicine with Islamic Complementary Medicine: A Preliminary Attempt in Malaysian Context - Hussin Supyan; Nur Azian Ab Rahman; Low Kok On (American Scientific Publishers, 2018)
Modern medicine has a long historical account. It is established through continuous series of contributions by many other disciplines. However, modern medicine does not provide answers and solutions to cure all diseases; otherwise it will not introduce the term idiopathic. When allopathy medicine failed to provide solutions to complicated disease that is related to jinn’ influence on the patients, then alternative medicine, complementary medicine, traditional healing, and Islamic complementary medicine (ICM) may be referred to. This paper discusses the bridging of modern medicine and ICM in dealing with six cases of patients who received treatments from both practices in Malaysia. These preliminary attempts have brought in positive results to the patients’ well-being and wellness.